Hip Hop and Hope : exploring the affordances of hip hop centred community music making for enhancing adolescents’ engagement with the field of water-related diseases in peri-urban community settings in KwaZulu-Natal, South Africa - Oosthuizen, Helen (University of Pretoria, 2018)
Dissertation (MMus)--University of Pretoria, 2017.